Lernen mit Geoinformation(ssystemen) aus der Perspektive deutscher Geographielehrer - Höhnle, Steffen; Schubert, Jan Christoph; Uphues, Rainer (Zeitschrift für Geographiedidaktik (ZGD), 2012)
Given Germany's low frequency of GI(S) use in its secondary schools' geography classrooms, we surveyed 410 teachers on their point of view of main impediments to wider implementation of GI-applications and the chances they see in the usage of GI(S) in the geography classroom. We did this in the framework of a larger cumulative mixed methods study which aims at improving the implementation of GI(S) in the classroom by developing well-founded implementation strategies and concrete measures for implementation. In this paper we present the results from the quantitative part of the study (impediments and chances from the point of view of the teachers) and later offer an overview of similar studies in other countries, followed by some concluding thoughts.